A Case Study Of Affin Bank Berhad - Krishnan, Chanthuru (2008)
This study focuses on the Affinbank Islamic banking that dedicated to offer quality products and services. The study is also able to provide relevant information to support the bank's vision , mission and goal. The fundamental research questions that related to the Affinbank Islamic banking was identified and reviewed.